A review of the parallel algorithms for solving multidimensional PDE problems - Alias, Norma; Islam, Md. Rajibul (Asian Network for Scientific Information (ANSINET), 2010)
This review study gives a widespread overview of the solutions of several engineering problems based on some multidimensional partial differential equations like parabolic, hyperbolic, elliptic, AGE, IADE equations. Different analytical methods of treatment as well as those of numerical methods are presented in this paper. Finally some evaluation phases of several experiments in order to solve some current engineering problems and recommendations are demonstrated